2021
DOI: 10.1021/acschembio.1c00232
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Human Guanine Deaminase Activity by an Emissive Guanine Analog

Abstract: Guanine deaminase (GDA) deaminates guanine to xanthine. Despite its significance, the study of human GDA remains limited compared to other metabolic deaminases. As a result, its substrate and inhibitor repertoire are limited, and effective real-time activity, inhibitory, and discovery assays are missing. Herein, we explore two emissive heterocyclic cores, based on thieno­[3,4-d]­pyrimidine ( thN) and isothiazole­[4,3-d]­pyrimidine ( tzN), as surrogate GDA substrates. We demonstrate that, unlike the thieno anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The applicability of other emissive nucleobases and nucleosides as potential substrates for metabolic enzymes was also evaluated with guanine deaminase (GDA) and cytidine deaminase (CDA), two hydrolytic zinc-based enzymes (Figure ). Marcela Bucardo showed that the emissive isothiazolo-guanine analog tz G N is an excellent substrate for human GDA (while th G N is not), facilitating real-time monitoring of deamination and its inhibition . Paul Ludford showed that th C, tz C, and even mth C were viable fluorescent substrates for CDA (Figure ).…”
Section: Emissive Rna Alphabetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of other emissive nucleobases and nucleosides as potential substrates for metabolic enzymes was also evaluated with guanine deaminase (GDA) and cytidine deaminase (CDA), two hydrolytic zinc-based enzymes (Figure ). Marcela Bucardo showed that the emissive isothiazolo-guanine analog tz G N is an excellent substrate for human GDA (while th G N is not), facilitating real-time monitoring of deamination and its inhibition . Paul Ludford showed that th C, tz C, and even mth C were viable fluorescent substrates for CDA (Figure ).…”
Section: Emissive Rna Alphabetsmentioning
confidence: 99%
“…Marcela Bucardo showed that the emissive isothiazolo-guanine analog tz G N is an excellent substrate for human GDA (while th G N is not), facilitating real-time monitoring of deamination and its inhibition. 61 Paul Ludford showed that th C, tz C, and even mth C were viable fluorescent substrates for CDA ( Figure 8 ). 62 …”
Section: Emissive Rna Alphabetsmentioning
confidence: 99%
“…Fluorescent, isomorphic and isofunctional purine and pyrimidine analogues derived from thieno[3,4‐ d ]‐pyrimidine and isothiazolo[4,3‐ d ]pyrimidine heterocyclic nuclei have been developed by replacing the imidazole ring with 5‐membered aromatic heterocycles [18–22] . Both emissive RNA alphabets exhibit significantly improved photophysical properties compared to their native counterparts as evidenced by their employment for analyzing enzymatic transformations and protein/nucleic acids interactions [23–28] . We have also explored the effect of exocyclic amine dialkylation on the fluorescence of both adenosine analogues [29] .…”
Section: Figurementioning
confidence: 99%
“…[18][19][20][21][22] Both emissive RNA alphabets exhibit significantly improved photophysical properties compared to their native counterparts as evidenced by their employment for analyzing enzymatic transformations and protein/nucleic acids interactions. [23][24][25][26][27][28] We have also explored the effect of exocyclic amine dialkylation on the fluorescence of both adenosine analogues. [29] Intriguingly, replacing the N 6 ,N 6 -dimethylamino with an azetidine dramatically increased the emission quantum yield of these purine mimics, particularly when strong electron-withdrawing groups were present at the 4-membered ring's 3-position [e.g., φ(H 2 O) = 0.64 for the 3,3-difluoroazetidine].…”
mentioning
confidence: 99%
“…[12,14] While the restoration of the nitrogen atom into the Hoogsteen face resulted in lower emission quantum yields, the higher degree of isofunctionality facilitated a near-identical behavior of the fluorescent probes compared to the thieno alphabet when studying N7-dependent processes. [12,[14][15][16][17][18] With these fluorescent nucleosides at our disposal, we opted to synthesize and explore the photophysical properties of N 6 ,N 6 dimethyladenine derivatives adopting both thieno-and isothiazolo-pyrimidines in place of the imidazole ring of the native purine (2 a and 2 b, Figure 1b and c), and assess their potential for generating emissive nucleoside analogs.…”
Section: Introductionmentioning
confidence: 99%